Brasstacks and beyond : perception and management of crisis in South Asia - Bajpal, Kanti P.; Bajpai, Kanti P.; University of Illinois at Urbana-Champaign. (New Delhi : Manohar, 1995)
With special reference to Brasstacks-related crisis between India and Pakistan.
"Under the auspices of the Program in Arms Control, Disarmament, and International Security, University of Illinois at Urbana-Champaign, Urbana, Illinois, USA."
0
0
0
0